Implementasi Nilai Tasamuh dan Ukhuwah Islamiyah dalam Pembelajaran Akidah Akhlak Kelas VII di MTs Negeri 1 Banyumas pada Masyarakat Multietnis: Analisis Interseksionalitas - Salma An Naafi; Muh Hanif (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study explores the implementation of tasamuh (tolerance) and ukhuwah Islamiyah (Islamic brotherhood) values in the teaching of Akidah Akhlak for seventh-grade students at MTs Negeri 1 Banyumas, a madrasah characterized by ethnic diversity. Using an intersectionality perspective, the research examines how religious, cultural, and social factors intersect and shape educational experiences. The chosen method is descriptive qualitative, with data collected through field observation, in-depth interviews with teachers, the head of the madrasah, and students, and document analysis. Data analysis followed stages of data reduction, presentation of findings, and conclusion. The results indicate that tasamuh and ukhuwah Islamiyah values are consistently integrated across the full cycle of teaching and learning, from lesson planning and classroom implementation to evaluation. Teachers cultivate tolerance by linking material to students’ social realities, using polite language, providing equal learning opportunities, and fostering respect for ethnic and social differences. Interactions among students occur harmoniously without signs of discrimination during the learning process. Beyond classroom practices, school culture initiatives such as the three-S program (smile, greet, and say hello) help strengthen an inclusive climate that centers human values in education. From an intersectionality standpoint, Akidah Akhlak instruction not only shapes students’ religious dimensions but also reinforces social relations within this multiethnic school environment. Keywords: Aqidah Akhlak, Intersectionality, Multiethnic Society, Tasamuh, Ukhuwah Islamiyah